PENYIMPANGAN MORAL TOKOH UTAMA DALAM NOVEL NEGERI DI UJUNG TANDUK KARYA TERE LIYE - Reski, Ahmad - (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by moral portrayed in literature. Foreign Novel on the Edge TereLiye work discusses the main character of moral aberrations, namely Thomas. The purpose of this study was to describe the main character in the moral perversion of State on the Edge novel works TereLiye. The moral aberrations associated with: (1) conscience, (2) freedom and responsibility, (3) values and norms, (4) the rights and obligations. This study is a qualitative study using descriptive methods. The result of this research is the discovery of the main character of moral aberration related to: (1) conscience, can be seen in the attitude of Thomas who pretend and declare statements are not honest when Thomas did an international conference in Hong Kong, (2) freedom and responsibility , can be seen from the attitude of Thomas who escaped from prison, (3) values and norms, can be seen in the attitude of Thomas who did the bribery case to launch his political actions.